Potentially pathogenic bacteria isolated from neglected air and surfaces in hospitals - Mayk Teles de Oliveira; Lorranny Mayara Silva Cunha; Fernanda Cardoso Cruz; Nathany Kelly Ribeiro Batista; Eric de Souza Gil; Virgínia Farias Alves; Maria Teresa Freitas Bara; Ieda Maria Sapateiro Torres (Universidade de São Paulo, 2021)
Hospital infections (HI) are a serious public health problem in many countries. Several studies have identified strains correlating to surgical site infections, many with multi-resistance. The goals of this study was to quantify, to identify and to verify the resistance profile of microorganisms collected at two hospitals settings, and to alert health professionals how environmental contamination can influence hospital infection rates. For air sampling in operating rooms, intensive care unit and materials sterilization center, the impaction method (Spin Air, IUL®) and passive sedimentation were used. For the isolation of bacteria on surfaces and uniforms contact plates (RODAC®) were used. Identification of the microorganisms was performed using Vitek® 2 Systems. The antibiograms were conducted according to the disk diffusion method recommended by CLSI. The surgical center of hospital B presented more than 500 CFU/m3 in aerial microbial load. In the aerial microbiota of the sampled areas of both hospitals, M. luteus, S. haemolyticus and S. hominis spp hominis were the prevalent microorganisms, with a percentage greater than 30%. On the surfaces and uniforms there was a prevalence of M. luteus (40%) and S. hominis spp hominis (20%) among others, and some of the resistant strains were isolated from environments with microbial load within the recommended limits.